Dual-band reconfigurable EBG loaded circular patch MIMO antenna using defected ground structure (DGS) and PIN diode integrated branch-lines (BLs). (31st May 2022) - Nikam, Pritam B.; Kumar, Jayendra; Sivanagaraju, V.; Baidya, Achinta
Abstract: In this work, a reconfigurable dual-band multiple-input–multiple-output (MIMO) antenna (RDMA) for the fifth generation (5G) 3.5 GHz and industrial, scientific and medical (ISM) 5.2 GHz has been reported. The reported antenna uses the partial ground plane defected ground structure (PGP-DGS) technique and the integration of the pin diode integrated branch lines ( B L s ) to obtain dual-band operation. Also, the intermediate structure, without DGS operates in wideband to narrowband reconfigurable mode. The operating frequency of the antenna can be tuned to other frequencies by changing the DGS and BLs design attributes. A novel mushroom inspired dual-band electronics bandgap structure is developed and characterized using a dispersion diagram. The proposed EBG is then placed between RDMA to obtain isolation better than −25 dB between closely packed (at λ 5 G / 17 . 14 ) antenna elements. The proposed antenna has an acceptable realized gain above 2.5 dBi and a stable end-fire radiation pattern with the main lobe at − 4 5 ∘ . Highlights: A novel single band to dual-band frequency reconfigurable antenna is developed and its characteristics have been measured. The proposed antenna exactly operates in the most demanding single industrial, scientific and medical (ISM) 5.2 GHz band or a dual fifth-generation (5G) and ISM 5.2 GHz bands. Defected-ground-structure (DGS) and modified CPW based frequency reconfiguration. Configuration also support narrowband to a wideband reconfigurable without DGS. Mushroom and meander line inspired dual-band EBG is proposed Antenna characteristics are measured and validated.